(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Public library, the local gate way to knowledge, provides a basic location for lifelong learning independent decision-making and cultural development of the individual and social groups. The primary purpose of the public library is to provide resources and services in a variety of media to meet the needs of individuals and groups for education, information and personal development including recreation and leisure. In the historical background of Kerala, Public libraries have an important role in the development and maintenance of democratic society by giving the individual access to a wide and varied range of knowledge, idea and opinions. This paper describes about the Historical role of Public Libraries and its present status in the Kerala state. In this study we reach a conclusion that the growth and role of Public Libraries in the State is bright and step-by-step progress is happening in the growth rate and in delivering different types of services to the society. Libraries are playing an active role in the social, cultural and educational development of the rural areas in state. The Kerala State Library Council has an on-going project to automate and network all the affiliated libraries moving in a positive path. The first phase aims to automate all the A+ and A grade libraries in Kerala State.